Prevalence and Factors Associated with Anxiety and Depression in Peruvian Medical Students - Piscoya-Tenorio, Jorge L. (2022)
“: During medical training, students are exposed to stressors that deteriorate mental health. This study determined depression and anxiety prevalence and their associated factors in students from four medical schools in northern Peru. A cross-sectional study was conducted among medical students from Lambayeque, Peru. The Goldberg Anxiety and Zung Depression tests were applied. The dependent variables were depression and anxiety, and their association with covariates (age, sex, type of university, socioeconomic level, experience, family problem, and physical activity) was evaluated. Prevalence ratios were calculated using generalized linear models. Of 482 students, the prevalence of anxiety was 61.8% and depression was 22.0%. A severe level of anxiety was observed in 6.2% in the group between 16 and 20 years old. It was observed that private university students had higher frequencies of having depression (PR = 2.01) and anxiety (PR = 1.35); males had a lower risk of anxiety (PR = 0.82), but higher risk of depression compared to females (PR = 1.45). Performing physical activity decreased the prevalence of depression (PR = 0.53); however, it increased the frequency of anxiety (PR = 1.26). Having family problems increased the prevalence of anxiety (PR = 1.26). Medical students from private universities experienced higher rates of depression and anxiety. Depression and anxiety were associated with gender and physical activity. These findings highlight the importance of mental health promotion due to its link with quality of life and academic performance.“